Voltage quality enhancement of distribution network based on unified power quality conditioner with BESS - Mei, Yan; Xu, Jiangbo; Peng, Chen; Kong, Weikang; Peng, Gang; Song, Guangyu (Frontiers in Energy Research, 2024)
This article proposes a voltage compensation control strategy for the distribution network based on the unified power quality conditioner (UPQC) with battery energy storage systems (BESS) to achieve comprehensive management of the power quality and improve the system dynamic responses. Specifically, aiming at that amplitude and phase jump of the terminal voltage, a capacity configuration compensation scheme is proposed to achieve voltage vector compensation. The series converter is designed to compensate for the amplitude and phase of the load voltage. The parallel converter is designed to realize power compensation and ensure that the grid voltage and current are sinusoidal and in phase. A voltage control approach based on the nonlinear disturbance observer (NDO) is developed for BESS to stabilize the DC bus voltage and improve the anti-interference performance of the current. An NDO is designed to accomplish current disturbance tracking and provide disturbance feedforward compensation. Simulations validate that the proposed approach is effective and feasible.